The power of algorithms and keys of participation - Esteves, José (Taylor and Francis Group, 2022)
The use of some technologies of the digital age present great challenges for our collective autonomy: the robots that take our work, the algorithms that direct our attention and social media that undermine our democracy. We live in the era of algorithms, which are the kings of algorithms usage, namely for content curation, user data collectionand content creation. This chapter describes the use of algorithms in social media. Social media services are the kings of algorithms usage, namely for content curation, user data collection, and content creation. First, we describe these main applications of social media algorithms. Then, we outline challenges of using algorithms in social media, in particular transparency and objectivity.
Keywords: 53 Ciencias Económicas; ODS 16 - Paz, justicia e instituciones sólidas